A retrospective study of calcineurin inhibitors in the treatment of idiopathic membranous nephropathy - CUI Lin-lin; YE Chao-yang (Linchuang shenzangbing zazhi)
Objective To observe the efficacy of calcineurin inhibitors in the treatment of the simple and the refractory idiopathic membranous nephropathy.Methods Seventy-two patients with idiopathic membranous nephropathy and regularly followed up in Changzheng Hospital of the Second Military Medical University were enrolled.There were 33 patients without remission after 6 months of angiotensin conversion enzyme inhibitor or angiotensin receptor blocker,and 39 patients without remission after 6 months of cyclophosphamiddum.These outpatients were regularly followed up with 24-h urinary protein,plasma albumin,serum creatinine,blood urea nitrogen,uric acid,cholesterol,triglyceride and blood concentration of calcineurin inhibitors.The therapeutic response of calcineurin inhibitors and the remission and recurrence rate of idiopathic membranous nephropathy were observed.The follow-up duration was 6 to 12 months.Results Of the 33 patients who received first immunosuppressive treatment,the cyclosporine A group had significant remission of 24-h urinary protein(F =36.36,P<0.000 1),plasma albumin(F = 20.81,P<0.000 1) and plasma cholesterol(F= 15.35,P = 0.001 5),and the tacrolimus group also had significant remission of 24-h urinary protein(F-40.06,P<0.01),plasma albumin(F = 34.42,P<0.000 1) and plasma cholesterol(F = 23.15,P<0.000 1).Of the 39 patients who have received cyclophosphamiddum treatment,the cyclosporine A group had significant remission of 24-h urinary protein(F = 46.6,P<0.000 1) and plasma albumin(F= 25.57,P<0.000 1),and the tacrolimus group also had significant remission of 24-h urinary protein(F= 51.5,P<0.000 1) and plasma albumin(F= 31.62,P<0.000 1).The remission rate was increased with time,but no significant difference was found between the two groups(P>0.05).Conclusions The calcineurin inhibitors combined with low-dose prednisolone treatment can be effective for either the simple idiopathic membranous nephropathy or the refractory idiopathic membranous nephropathy.The difference between the two kinds of calcineurin inhibitors has no statistically significant difference.The adverse reaction can be low-graded and regulated.